Pengaruh Pemberdayaan Istri Nelayan Melalui Industri Kecil dan Motivasi Ketrampilan Terhadap Peningkatan Kesejahteraan SDM - Evyana Diah Kusumawati; Karjono Karjono (Majalah Ilmiah Bahari Jogja, 2022)
This study aims to determine the effect of the level of empowerment of fisher wives through small industries on increasing the welfare of fishers’ families in Wonosari village, to determine the effect of growing motivational skills on improving the welfare of human resources of fishers’ families in Wonosari village and to determine the effect of the level of empowerment of fishers’ wives through small industries and growing motivation. skills to improve the welfare of human resources for fishing families in Wonosari village. The population in this study was the wives of fishermen from the village of Wonosari 500 people. Data collection by questionnaire method. This instrument was tested on 50 fishermen's wives in Wonosari village. Data analysis used is a multiple regression analysis techniques. Before data analysis, the analysis requirements test was conducted, including normality, heteroscedasticity, and autocorrelation tests. The results of this study are: the results of the partial correlation test between the variables X1 and Y are significant and have a positive effect of 55.1%. The relationship between X2 and Y is significant and has a positive effect of 80.5%. However, the relationship between X1 and X2 variables with Y as a control variable is not significant and has a negative effect of 87.5%.